2017
DOI: 10.1097/jcn.0000000000000342
|View full text |Cite
|
Sign up to set email alerts
|

Is There Inequity in Hospital Care Among Patients With Acute Coronary Syndrome Who Are Proficient and Not Proficient in English Language?

Abstract: These results suggest that LEP patients admitted to Australian or New Zealand hospitals with suspected ACS may not experience inequity in hospital care and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…After title and abstract review, 70 manuscripts were identified for full-text review. After full-text review, 29 studies met the inclusion criteria (eTable 2 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After title and abstract review, 70 manuscripts were identified for full-text review. After full-text review, 29 studies met the inclusion criteria (eTable 2 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported findings from academic hospital settings and community hospitals. Eighteen of 29 studies were performed at a single center, whereas 5 studies were multicenter and 6 studies used a statewide or nationwide database (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations